KONSEKSTUALITAS HUKUM ISLAM DI INDONESIA; Studi Terhadap Hukum Wakaf - Achmad Irwan Hamzani (Faculty of Law, Universitas Diponegoro, 2014)
The law waqf including parts of Islamic law in Indonesia dynamic and contextual. Many if the new provisions that have not been there before, some even ouside the mainstream understanding. Contextuality of Islamic law in the field of waqf can be a good example in the framework of exploring and developing other areas of law that Islamic law is always relevant. Islamic law to be resistant to the times that suit for every age and penetrate the territorial limits.